Thoracic complications of echinococcosis. Round table - Galarraga, José; Soto Cordano, José; di Leoni, Francisco; Tchekmedyian, Vartan; Lorenzelli, Juan A; Chifflet, Juan (Cirugía del Uruguay, 1994)
We thank the authorities of the XXXIX Congress Uruguayan Surgery the honor that has given us to coordinate this Round Table. Before entering to strictly deal with the issue, we believe it convenient make some considerations that are fundamental and mandatory since without it we would be ignoring one of the most serious problems this topic requested by colleagues, to be considered in this Congress.